Pembangunan Kit Amali Geseran Dalam Paip Bagi Kursus Mekanik Bendalir di Politeknik - Samsuri, Siti Salwa; Abd Rahman, Nor Ruzanna; Murad, Siti Rohanah (J-Innovation, 2024)
Fluid Mechanics is a core course in the curriculum structure of the Diploma in Mechanical Engineering at the Polytechnic. The main component of this course consists of theory and practical related topics in Fluid Mechanics. The practical equipment used must be complete and meet the requirements of the syllabus. The main objective of this study is to develop a pipe friction practical kit for the Fluid Mechanics course and make an analysis to obtain the value of the friction coefficient from the developed kit. Some of the parameters that are studied to obtain the value of energy loss are changes in pipe diameter, flow velocity and pipe length. As a result of the findings, the main factor that affects the value of the friction coefficient is the fluid flow velocity in the pipe. In conclusion, this developed kit has achieved the set objectives and is a teaching aid for practice in the Fluid Mechanics course.